2012
DOI: 10.1248/cpb.c12-00363
|View full text |Cite
|
Sign up to set email alerts
|

Improved Method for the Solid-Phase Synthesis of Oligoribonucleotide 5′-Triphosphates

Abstract: We have developed an improved solid-phase method for the synthesis of 5′-triphosphates (5′-TPs) of oligoribonucleotides. The method is based on the use of salicyl phosphorochloridite as the phosphitylating reagent and the improvement is characterized by the use of the highly reactive pyrophosphorylating reagent tris(tetra-n-butylammonium) hydrogen pyrophosphate instead of the conventional tri-n-butylammonium salt for the nucleophilic substitution reaction to form the cyclic ester intermediate. The improved met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Following the methodd eveloped by Ludwiga nd Eckstein, [12] Nagata et al showed that as olid-phase-bonded 25 mer RNAoligonucleotide could be phosphitylated using 2-chloro-4H-1,3,2-benzodioxaphosphorin-4-one (salicyl phosphorochloridite method) which was subsequently reactedw ith pyrophosphate to yield a5 '-cyclotriphosphitylated oligonucleotide followed by oxidation to give the 5'-triphosphate. [15] When tris(tetra-n-butylammonium) hydrogen pyrophosphate was used, the major product was the desired 5'-triphosphate with still as ignificant amount of 5'-OH and5 '-phosphonate oligonucleotide. However,w hen bis(tri-n-butylammonium)d ihydrogen pyrophosphate was used only al ow triphosphorylation efficiency was observed.I nt his case high amounts of the 5'-phosphonate were obtained.…”
mentioning
confidence: 99%
“…Following the methodd eveloped by Ludwiga nd Eckstein, [12] Nagata et al showed that as olid-phase-bonded 25 mer RNAoligonucleotide could be phosphitylated using 2-chloro-4H-1,3,2-benzodioxaphosphorin-4-one (salicyl phosphorochloridite method) which was subsequently reactedw ith pyrophosphate to yield a5 '-cyclotriphosphitylated oligonucleotide followed by oxidation to give the 5'-triphosphate. [15] When tris(tetra-n-butylammonium) hydrogen pyrophosphate was used, the major product was the desired 5'-triphosphate with still as ignificant amount of 5'-OH and5 '-phosphonate oligonucleotide. However,w hen bis(tri-n-butylammonium)d ihydrogen pyrophosphate was used only al ow triphosphorylation efficiency was observed.I nt his case high amounts of the 5'-phosphonate were obtained.…”
mentioning
confidence: 99%